Inner-City Transformations after Socialism. Findings from Interviews with New Residents of Pre-War Tenement Houses in Gdańsk - Grabkowska, Maja (Bulletin of Geography. Socio-economic Series, 2011)
Issues of intense suburbanization and urban sprawl have been the most discussed threads in the recent debate on urban development in Poland. Meanwhile, in numerous cities of Western Europe signs of inner-city revival have been observed and investigated. Led by demographic and lifestyle changes alike, such reurbanization trends are found to be closely related to household transformations. Results of undertaken studies indicate that residential preferences of non-traditional households, such as singles, cohabitations, childless couples or flatsharers, gravitate to inner-city living. The aim of this paper is to reveal similar tendencies in a postsocialist city, using the example of Gdańsk. Presented results of statistical and qualitative data analyses point towards confirmation of incipient reurbanization, although with several distinctions following from the postsocialist context.